To Be Human is to Be Better: A Discussion with Julian Savulescu - Savulescu, Julian; Giannopoulou, Phaedra (Conatus - Journal of Philosophy, 2025)
In this paper, Julian Savulescu discusses humanity’s trajectory – past, present, and future. As the world undergoes relentless transformation driven by technological advancements, some pressing questions arise: Is it time to provide modern solutions to old problems such as discrimination, inequality, and crime? Should people retain absolute autonomy over their decisions, even in the case that their judgment may falter? What role is Artificial Intelligence going to play in our day-to-day lives, and how far could it go? This dialogue unveils a visionary blueprint for humanity, regarding how much could really be achieved with the help of technology, what are some of the difficult decisions we would have to make, and ultimately what would it look like if we tried to use the tools we have to actually create a society that values justice and equality above individual freedom.